PENCIPTAAN BUDAYA RELIGIUS PERGURUAN TINGGI ISLAM (Berkaca Nilai Religius UIN Maulana Malik Ibrahim Malang) - Almuâ€™tasim, Amru (J-PAI: Jurnal Pendidikan Agama Islam, 2016)
During these universities only produce graduates who only have a certain skill, while they do not have personal integrity as a member of the family, community, and religious citizens. This situation will greatly affect the education system in universities. Where the College as an organization of higher education is a means of cooperation group of people (Higher Education and Society) to achieve the desired objectives. Achievement of the goal Universities, both in quality and quantity depends on the people who gathered at the agency. if the increase is not accompanied by planting intellectual Islamic values are embodied in building religious culture in the Universities, the national education goals will not be achieved well.Â Keywords: Religious, Culture, Higher Education